Kampanye Jakarta Bersih untuk Meningkatkan Kesadaran Masyarakat agar Tidak Membuang Sampah Sembarangan pada saat CFD di Bundaran HI - Anita Fitri Wahyudi; Dinah Ainiyyah; Kirana Safira; Safira Aprilia; Dini Safitri (Universitas Mathla'ul Anwar Banten, 2020)
THE JAKARTA BERSIH CAMPAIGN TO RAISE PUBLIC AWARENESS SO AS NOT TO DISPOSE OF LITTER DURING CFD AT THE HI ROUNDABOUT. Car Free Day is an activity held every Sunday. It was held on May 23, 2002. Currently it continues for 5 hours starting from 06.00 - 11.00 WIB. Car Free Day aims to socialize to the public to reduce private vehicles so that people are interested in using public transportation. The implementation is along the road in the Central Jakarta area, precisely around Senayan - Monas. People who take part in this activity usually spend time exercising, selling, or running their community activities. The various activities carried out on the car free day cause a lot of waste. Not all visitors of the car free day are aware of the importance of keeping the environment clean. On May 5, 2019 we held a campaign called